Balloon dielectric elastomer actuator speaker. (May 2019) - Hosoya, Naoki; Masuda, Hiroaki; Maeda, Shingo
Graphical abstract: Highlights: Establishment of a balloon speaker using dielectric elastomer actuator. Realization of nearly spherical shape with a 3033% increase in surface area. Allowing a low voltage operation (800 V p-p) and audible frequency range (∼16 kHz). Elucidation of a relationship between acoustic radiation pattern and vibrational mode shape. Abstract: A balloon dielectric elastomer actuator (DEA) speaker is constructed by forming a disk-shaped DEA film into a sphere using air, increasing its surface area by 3033%. Sound is generated via expansion and contraction. Shaping the DEA film into a sphere decreases the film thickness and applies a significant amount of pre-strain (prestretch) to the film. In the experiment, sound pressure levels in an audible frequency response up to 16 kHz is the approximately same as both our previous hemispherical DEA speaker and this balloon DEA speaker, allowing an actuating voltage of the balloon speaker lower (800 V p-p signal with an offset of 400 V) than that of our previous hemispherical DEA speaker (2 kV). This is the first time to achieve the audible frequency response of the acrylic balloon DEA speaker. Furthermore, the acoustic radiation pattern of the speaker extends over a 270° range. Compared to polyhedron loudspeakers, which are currently used as omnidirectional sound sources in general acoustic tests, a balloon DEA speaker is compact and lightweight. Therefore, balloon DEA speakers have sufficient potential to contribute to the proper assessment of indoor acoustic characteristics using a scale model.